Dynamic microbiome and mobile resistome are revealed in river biofilms from a multi-use watershed through long-read sequencing - Mills, Molly; Wittum, Thomas; Lee, Jiyoung (Frontiers in Environmental Science, 2024)
The dissemination of antibiotic resistance (AR) through various environments and the role of AR hotspots in public health crises are gaining increasing attention. Aquatic biofilms are speculated to play a significant role in AR spread due to their collection of diverse microorganisms and facilitation of horizontal gene transfer (HGT). However, few studies have characterized the AR genes (resistome) present in natural river biofilms. The goal of this study was to use MinION long-read sequencing to analyze the microbiome, resistome, and mobile genetic elements (MGEs) in periphyton (epilithic biofilms) (n = 56) from a multiuse watershed in Ohio, to elucidate the role of periphyton in clinically relevant AR. Key members of the periphyton microbiome included Flavobacterium and Aeromonas. Overall, periphyton microbial communities shifted with season and location. Specifically, species of Porphytrobacter and Cyanobacteria were more abundant in biofilms during the summer season. Potentially pathogenic bacteria, including the family Enterobacteriaceae, the fish pathogen Pseudomonas koreensis, and the human pathogen Shigella flexneri, were more abundant in sites downstream of the large city, Columbus, OH, than upstream. The periphyton resistome carried diverse AR genes for a variety of classes, but had minimal clinical relevance. Escherichia, E. coli, and Muvirus were common hosts of AR genes (ARGs) and MGEs. Pseudomonas and Cyanobacteria were frequently MGE hosts, but not AR genes, indicating the potentially important role of these taxa in HGT within and around biofilms. While the sequencing depth in this study was relatively shallow, these findings highlight the mobility potential for the transmission of ARGs in river biofilms.